KAP study on bio-medical waste management among interns in a tertiary care hospital in Maharashtra - Pandey, Aastha; Dardi, Charan Kaur (International Journal Of Community Medicine And Public Health, 2017)
Background: Biomedical Waste Management is Hazardous and can lead to many infections and diseases. Interns are the future physicians of tomorrow and they should be conscious about safe disposal and segregation practices. So, the present study was undertaken to assess the knowledge and awareness about Biomedical waste management in Interns. The aims and objectives were to assess the knowledge and awareness about biomedical waste management in Interns. Methods: This cross sectional study was carried out in 51 interns. A pretested self-administered questionnaire on BMW management was given to the interns. Results: Out of 51 interns 26 were girls and 25 were boys. 63% knew correct definition of biomedical waste. 23.5% said that authorization is required by CPCB. 15% had undergone training but 60% were keen to attend training programme. 86% had correct knowledge about sources of generation of BMW and 94% had knowledge of Biohazard symbol. Only 68% had knowledge of segregation of waste but none had knowledge of correct colour coding. 88% answered that record maintenance was essential for biomedical waste management. 94% said that BMW is teamwork. Conclusions: There is a need for rigorous training programme for interns and monitoring is needed.